2007
DOI: 10.1158/0008-5472.can-06-3304
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 Expression in Pancreatic Carcinoma Cells as a Novel Mechanism of Immune Evasion in Cancer

Abstract: The forkhead transcription factor Foxp3 is highly expressed in CD4+CD25+ regulatory T cells (Treg) and was recently identified as a key player in mediating their inhibitory functions. Here, we describe for the first time the expression and function of Foxp3 in pancreatic ductal adenocarcinoma cells and tumors. Foxp3 expression was induced by transforming growth factor-B2 (TGF-B2), but not TGF-B1 stimulation in these cells, and was partially suppressed following antibody-mediated neutralization of TGF-B2. The T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
290
2
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(316 citation statements)
references
References 37 publications
19
290
2
5
Order By: Relevance
“…Nothing is known about the role of the Treg-attracting chemokine CCL22 in these tumors. 36,37 We found that the majority of HCC and all pancreatic cancer samples were infiltrated with CCL22-expressing immune cells. We show here for the first time that tumor cells potently induce CCL22 secretion in leukocytes.…”
Section: Discussionmentioning
confidence: 87%
“…Nothing is known about the role of the Treg-attracting chemokine CCL22 in these tumors. 36,37 We found that the majority of HCC and all pancreatic cancer samples were infiltrated with CCL22-expressing immune cells. We show here for the first time that tumor cells potently induce CCL22 secretion in leukocytes.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, we observed FOXP3 + cell infiltration in most of the tumours. Recent studies have reported the expression of FOXP3 mRNA and protein in a limited number of pancreatic carcinoma cells, cell lines [54], and other tumour cell lines of several origins, including breast cancer [55].…”
Section: Discussionmentioning
confidence: 99%
“…In the first one, FOXP3 expression was restricted to the tumor cells. Normal pancreatic duct cells were devoid of FOXP3 expression, but FOXP3 was detected by immunohistochemistry in human pancreatic cancer cells (Hinz et al, 2007). Cancer cell staining was cytoplasmic in most patients, whereas in others, it was predominantly nuclear.…”
Section: Foxp3 Expression In Normal and Cancerous Human Cellsmentioning
confidence: 95%
“…A nuclear localization of FOXP3 was also reported for most human normal and cancer cells expressing this factor (Zuo et al, 2007b;Ebert et al, 2008;Wang et al, 2009). However, a predominant cytoplasmic FOXP3 labeling was reported for human pancreatic cancer cells (Hinz et al, 2007). In a recent work dealing with two large series of breast cancer specimens, immunohistological FOXP3 staining was localized predominantly in the tumor cell cytoplasm, whereas a few specimens showed only nuclear staining (Merlo et al, 2009).…”
Section: Antioncogenic Effect Of Foxp3mentioning
confidence: 96%